Transient expression of GUS gene in Malaysian rice callus following bombardment - Nurul Natasha Hyder Shahril, 1991- 605101; Alina Wagiran 465169; Fakulti Biosains dan Kejuruteraan Perubatan 538915 (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2014)
Project Paper (Sarjana Muda Sains (Biologi Industri)) - Universiti Teknologi Malaysia, 2014